1997
DOI: 10.1007/s001040050178
|View full text |Cite
|
Sign up to set email alerts
|

Minimal-invasive Chirurgie und Tumorchirurgie – Palliative laparoskopische Techniken

Abstract: The oncological principles of radical tumor surgery are not proven to be successfully applied with today's laparoscopic techniques. The value of minimal invasive surgery has to be critically evaluated for the radical (R0) resection of malignant tumors. On the other hand, there is an indication for laparoscopic palliation in order to minimize the surgical trauma. Many publications have demonstrated the technical feasibility with acceptable morbidity and mortality and a decreased hospital stay. For different rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
6
Order By: Relevance
“…Numerous authors are skeptical of the feasibility of laparoscopic tumor resection due to the higher risk of spreading malignant cells, small safety margins, and undiscovered secondary neoplasms [18,19,23], often explicitly discussing the problem of possible port-site metastases [11,15,17,18]. In this study, our goal was to evaluate the long-term outcome of laparoscopic partial liver resection due to a malignant tumor in relation to the gas used for the creation of pneumoperitoneum (CO 2 , helium, and air).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors are skeptical of the feasibility of laparoscopic tumor resection due to the higher risk of spreading malignant cells, small safety margins, and undiscovered secondary neoplasms [18,19,23], often explicitly discussing the problem of possible port-site metastases [11,15,17,18]. In this study, our goal was to evaluate the long-term outcome of laparoscopic partial liver resection due to a malignant tumor in relation to the gas used for the creation of pneumoperitoneum (CO 2 , helium, and air).…”
Section: Discussionmentioning
confidence: 99%
“…The more extensive use of helium in experimental and, occasionally, clinical laparoscopy has led to further investigation of this gas. Various studies have shown significantly lower rates of tumor growth in a helium environment than in room air or CO 2 surrounding [5-7, 15, 16, 20, 21], which has been discovered both in vitro and in vivo [6,15,16,19]. The mechanisms of this reduction of tumor growth remain unclear; however, it has been suggested that an enhancement of malignant growth and spread under the influence of CO 2 is more responsible than a tumor growth-suppressing effect of helium.…”
Section: Discussionmentioning
confidence: 99%
“…Dennoch wurden bis heute nur kleine Serien über die Palliation des nicht resektablen stenosierenden Magenkarzinoms mittel MIC publiziert [40,45].Auch bei Magenausgangsstenose durch einen lokal fortgeschrittenen Pankreaskopftumor ist eine Gastroenterostomie mit Braun-…”
Section: Palliativeingriffeunclassified
“…Das geringe Operationstrauma ermöglicht die Beschleunigung der Rekonvaleszenz und damit die Verkürzung des postoperativen Krankenhausaufenthaltes [27,28] …”
Section: Palliative Laparoskopische Verfahrenunclassified